1995
DOI: 10.1016/0092-8674(95)90478-6
|View full text |Cite
|
Sign up to set email alerts
|

The mei-41 gene of D. melanogaster is a structural and functional homolog of the human ataxia telangiectasia gene

Abstract: The D. melanogaster mei-41 gene is required for DNA repair, mitotic chromosome stability, and normal levels of meiotic recombination in oocytes. Here we show that the predicted mei-41 protein is similar in sequence to the ATM (ataxia telangiectasia) protein from humans and to the yeast rad3 and Mec1p proteins. There is also extensive functional overlap between mei-41 and ATM. Like ATM-deficient cells, mei-41 cells are exquisitely sensitive to ionizing radiation and display high levels of mitotic chromosome ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
172
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(179 citation statements)
references
References 39 publications
6
172
1
Order By: Relevance
“…The essential MEC1/ ERS1 protein is required for the majority of responses observed in S. cerevisiae including the DNA replication and damage checkpoint pathways, transcriptional activation of DNA damage-responsive genes, meiotic recombination and DNA repair (Weinert et al, 1994;Kato and Ogawa, 1994). Structural and functional homologs of MEC1 include the Drosophila melanogaster Mei-41 protein, the S. Pombe Rad3 protein, and the mammalian AT-and Rad3-related ATR/FRP1 protein (Hari et al, 1995;Bentley et al, 1996;Cimprich et al, 1996). The closest homolog to ATM in sequence similarity is the S. cerevisiae TEL1 gene product, deletions of which results in the shortening of telomeres (Morrow et al, 1995;Greenwell et al, 1995).…”
Section: Atm Proteinmentioning
confidence: 99%
“…The essential MEC1/ ERS1 protein is required for the majority of responses observed in S. cerevisiae including the DNA replication and damage checkpoint pathways, transcriptional activation of DNA damage-responsive genes, meiotic recombination and DNA repair (Weinert et al, 1994;Kato and Ogawa, 1994). Structural and functional homologs of MEC1 include the Drosophila melanogaster Mei-41 protein, the S. Pombe Rad3 protein, and the mammalian AT-and Rad3-related ATR/FRP1 protein (Hari et al, 1995;Bentley et al, 1996;Cimprich et al, 1996). The closest homolog to ATM in sequence similarity is the S. cerevisiae TEL1 gene product, deletions of which results in the shortening of telomeres (Morrow et al, 1995;Greenwell et al, 1995).…”
Section: Atm Proteinmentioning
confidence: 99%
“…It has been suggested that an ATM-like protein has a critical role in maintaining chromosome condensation in the vicinity of recombination intermediates (Hawley and Friend, 1996). In support of the role of ATM gene in chromosome condensation, it has been reported that mei-41 mutants of Drosophila melanogaster (homologue of ATM gene) exhibit di used chromatin (Hari et al, 1995). The ATM gene encodes a protein kinase that is distantly related to the yeast MEC1 and TEL1 proteins that function in maintaining the integrity of telomeres (Greenwell et al, 1995;Morrow et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PIK family includes the TOR proteins, which are targets of the FKBP-rapamycin complex (Brown and Schreiber, 1996;Hall, 1996), and the ataxia telangiectasia gene product, ATM (Savitsky et al, 1995). A subset of the PIK family contains an additional region of homology termed the rad3 homologous region, and this subfamily includes the S. cerevisiae MEC1 and TEL1 (Greenwell et al, 1995;Morrow et al, 1995) and the Drosophila mei-41 gene product (Hari et al, 1995). Mutants in mec1, mei-41 and rad3 all display increased radiation sensitivity and are de®cient in cell cycle checkpoints which prevent mitosis in the presence of unreplicated or damaged DNA.…”
Section: Introductionmentioning
confidence: 99%